2018
DOI: 10.1097/mcg.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sleep and Coexistent Psychopathology Have Significant Impact on Fatigue Burden in Patients With Inflammatory Bowel Disease

Abstract: Because fatigue is common in IBD patients, these findings suggest that attention to quality of sleep and psychopathology is as important as medical disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
3
25
0
1
Order By: Relevance
“…Fatigue is caused by a complex interaction between medication side effects, poor nutrition, depressive symptoms and inflammation, among others. Other survey-based studies have correlated sleep disturbance in IBD patients to fatigue 2,31 . A systematic approach is required to treat fatigue in patients with IBD, which has a sizeable chance of improving QOL for our IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is caused by a complex interaction between medication side effects, poor nutrition, depressive symptoms and inflammation, among others. Other survey-based studies have correlated sleep disturbance in IBD patients to fatigue 2,31 . A systematic approach is required to treat fatigue in patients with IBD, which has a sizeable chance of improving QOL for our IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep plays an important role in patients with IBD. Previous studies have confirmed that good sleep can help reduce fatigue, improve quality of life and alleviate gastrointestinal symptoms in patients with IBD (9,10). In IBD patients, the relationship between sleep, and mucosal activity and recurrence has been confirmed (11,12).…”
Section: Introductionmentioning
confidence: 85%
“…In a cross‐sectional study of 131 patients with IBD, elevated CRP, also using a standard‐sensitivity assay, was associated with 3·16 greater adjusted odds of poor sleep, although numbers were small . In a recent cross‐sectional study of 631 adults with IBD, the presence of significant fatigue was associated with marginally elevated CRP and ESR in UC patients but not CD . However, these results are limited by nearly 40% missing data on inflammation and the standard‐sensitivity CRP assay used.…”
Section: Depressive Symptoms or Somatic Symptoms?mentioning
confidence: 98%